2021
DOI: 10.1016/j.crphys.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The infant gut microbiota at 12 ​months of age is associated with human milk exposure but not with maternal pre-pregnancy body mass index or infant BMI-for-age z-scores

Abstract: Background: As obesity rates continue to rise, it is increasingly important to understand factors that can influence body weight and growth, especially from an early age. The infant gut microbiota has broad effects on a variety of bodily processes, but its relation to infant growth is not yet fully characterized. Since the infant gut microbiota is closely related to breastfeeding practices and maternal health, understanding the relationship between these factors and infant growth may provide insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Obesity is one of the most prevalent non-communicable diseases worldwide as well as in pediatric patients. Therefore, it is important to understand the potential causes to reduce the prevalence and associated morbidities [ 61 ]. In this regard, the mode of delivery, maternal health, antibiotic exposure, and breastfeeding are considered as factors that play a pivotal role in altering the infant gut microbiota and, subsequently, the probability of obesity onset in children [ 61 ].…”
Section: Microbial Dysbiosis: a “Trigger Point” For Children’s Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is one of the most prevalent non-communicable diseases worldwide as well as in pediatric patients. Therefore, it is important to understand the potential causes to reduce the prevalence and associated morbidities [ 61 ]. In this regard, the mode of delivery, maternal health, antibiotic exposure, and breastfeeding are considered as factors that play a pivotal role in altering the infant gut microbiota and, subsequently, the probability of obesity onset in children [ 61 ].…”
Section: Microbial Dysbiosis: a “Trigger Point” For Children’s Healthmentioning
confidence: 99%
“…Therefore, it is important to understand the potential causes to reduce the prevalence and associated morbidities [ 61 ]. In this regard, the mode of delivery, maternal health, antibiotic exposure, and breastfeeding are considered as factors that play a pivotal role in altering the infant gut microbiota and, subsequently, the probability of obesity onset in children [ 61 ]. It has been demonstrated that breastfed infants have a lower incidence and risk of obesity than formula-fed infants.…”
Section: Microbial Dysbiosis: a “Trigger Point” For Children’s Healthmentioning
confidence: 99%
“…Taking together all the information available, breast milk has been considered as a probiotic food for infants 99 . Understanding, bacterial colonization patterns related to solid food intake will enable personalized nutrition to prevent obesity in childhood, 100 where maternal lactation until 12 months appears as more important than BMI of the mother/child 101 …”
Section: Perinatal Infancymentioning
confidence: 99%
“…Although maternal pre-pregnancy BMI was associated with significantly greater infant gut microbial diversity (Chao1, p = 0.01; Shannon, p = 0.04), a bivariate analysis revealed that human milk exposure was the likely driver of this observed association (Chao1, p = 0.03; Shannon, p = 0.07), and not maternal BMI (Chao1, p = 0.49; Shannon, p = 0.54). At 12 months of age, infant BMI-for-age z-scores were only significantly related to maternal pre-pregnancy BMI (p = 0.01), and not human milk exposure (p = 0.53) or the infant gut microbiota (Chao1, p = 0.95; Shannon, p = 0.10; Bray-Curtis, p = 0.90; Sorensen, p = 1) [23].…”
Section: Infant Growth and The Gut Microbiota At 12 Monthsmentioning
confidence: 91%